2002
DOI: 10.1002/gcc.10111
|View full text |Cite
|
Sign up to set email alerts
|

The role of Alu repeat clusters as mediators of recurrent chromosomal aberrations in tumors

Abstract: There is increasing evidence for the involvement of repetitive DNA sequences as facilitators of some of the recurrent chromosomal rearrangements observed in human tumors. The high densities of repetitive DNA, such as Alu elements, at some chromosomal translocation breakpoint regions has led to the suggestion that these sequences could provide hot spots for homologous recombination, and could mediate the translocation process and elevate the likelihood of other types of chromosomal rearrangements taking place. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
184
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(196 citation statements)
references
References 158 publications
7
184
2
Order By: Relevance
“…A correlation study of Alu density and breakpoint cluster on chromosome 22 demonstrated that cancer-related breakpoints are exclusively mapped to regions with Alu density higher than 20%. At the same time, regions of high Alu density without known breakpoints are also present (Kolomietz et al, 2002). Regions of high Alu density with low rearrangement frequency are also observed in our analysis, such as intron 5 in MSH2 and intron 15 in MLH1 (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A correlation study of Alu density and breakpoint cluster on chromosome 22 demonstrated that cancer-related breakpoints are exclusively mapped to regions with Alu density higher than 20%. At the same time, regions of high Alu density without known breakpoints are also present (Kolomietz et al, 2002). Regions of high Alu density with low rearrangement frequency are also observed in our analysis, such as intron 5 in MSH2 and intron 15 in MLH1 (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Our study of germ-line mutations among HNPCC patients suggests an important contributory role for Alu sequences in the type and frequency of genomic rearrangements. For both loci of MLH1 and MSH2, the average Alu density at the intronic regions are above 20%, which is often observed at cancer-related regions (Kolomietz et al, 2002). Among the introns, the highest density of breakpoints is co-localized with the highest Alu density; intron 6 of MLH1 and intron 2 of MSH2, respectively (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The involvement of Alu elements in recombination is reported as one of the causes of human genetic diseases, including tumors. 30,31 Although the precise structure of this region is still unknown, a possible mechanism of the large deletion and inversion is illustrated in Figure 3c. Application of a high-density SNP mapping microarray analysis enables us to detect deletions and amplifications at a genome-wide level.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the results discussed here focus on the beneficial effects of Alu element insertion, the same process could also be detrimental for the organism. By inserting into essential genes, Alu elements can indeed annihilate important physiological functions; moreover, because of their high level of sequence homology, they can also mediate important disease-causing genomic rearrangements [76]. The duality of the effect of Alu element insertion demonstrates that Alu amplification has not been a neutral process; on the contrary, that it has been actively participating in genome evolution.…”
Section: Resultsmentioning
confidence: 99%